SOSIALISASI SOFTWARE ACCURATE ACCOUNTING KEPADA SISWA SMAN 1 RANCAH CIAMIS-JAWA BARAT - Giovanny Bangun Kristianto; RR Farida Istiningrum; Lusi Yuliarti (Sekolah Tinggi Ilmu Ekonomi AMA, 2022)
Accounting is one of the financial procedures that should be prepared by every business that is carried out. However, accounting is also useful for learning for the academic world. The world of technology is developing, so that accounting is currently being updated with an accounting system, which will make it easier for users to compile accounting reports more precisely. In this community service, the participants are students of SMAN 1 Rancah, Ciamis, West Java. The material given is the socialization of the Accurate Accounting system. Accurate Accounting is a software that is able to help its users to compile a complete, informative and easy to use accounting financial report. So that the material provided will be easily absorbed by the participants. Constraints faced such as the lack of knowledge about basic accounting and ignorance of the Accurate Accounting software became the basis for community service to be carried out. The limited implementation time can be an important concern, because the scope of the accounting world is quite broad, starting from the basics of accounting and developing accounting as a system within the company and becoming an excellent learning medium for educational development. Keywords: financial statement, accounting, accurate, system